2014
DOI: 10.1088/0004-637x/787/1/91
|View full text |Cite
|
Sign up to set email alerts
|

The First Gamma-Ray Bursts in the Universe

Abstract: Gamma-ray bursts (GRBs) are the ultimate cosmic lighthouses, capable of illuminating the universe at its earliest epochs. Could such events probe the properties of the first stars at z ∼ 20, the end of the cosmic Dark Ages? Previous studies of Population III GRBs only considered explosions in the diffuse relic H II regions of their progenitors, or bursts that are far more more energetic than those observed to date. But the processes that produce GRBs at the highest redshifts likely reset their local environmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 128 publications
(126 reference statements)
1
42
0
Order By: Relevance
“…Although X-rays from these events may be detected by Swift or its successors such as the Joint Astrophysics Nascent Universe Satellite (JANUS; Mészáros & Rees 2010;Roming 2008;Burrows et al 2010), their afterglows ) might also be detected in all-sky radio surveys by the Extended Very Large Array (eVLA), eMERLIN, and the Square Kilometer Array (SKA; de Souza et al 2011). We are now studying detection limits for Pop III GRBs in a variety of circumstellar environments (Mesler et al 2012(Mesler et al , 2013.…”
Section: Resultsmentioning
confidence: 99%
“…Although X-rays from these events may be detected by Swift or its successors such as the Joint Astrophysics Nascent Universe Satellite (JANUS; Mészáros & Rees 2010;Roming 2008;Burrows et al 2010), their afterglows ) might also be detected in all-sky radio surveys by the Extended Very Large Array (eVLA), eMERLIN, and the Square Kilometer Array (SKA; de Souza et al 2011). We are now studying detection limits for Pop III GRBs in a variety of circumstellar environments (Mesler et al 2012(Mesler et al , 2013.…”
Section: Resultsmentioning
confidence: 99%
“…Mesler et al 2014). We assume an explosion energy of ESN = 1.2 × 10 51 erg for all SNe, use the ejecta masses by Heger & Woosley (2002), and the individual metal yields by Heger & Woosley (2010).…”
Section: Chemical Feedbackmentioning
confidence: 99%
“…Non-rotating Pop III stars from 10 -40 M die as core-collapse supernovae (CC SNe) and 90 -260 M stars can explode as pair-instability (PI) SNe (Barkat et al 1967;Glatzel et al 1985;Heger & Woosley 2002Chatzopoulos & Wheeler 2012;Chatzopoulos et al 2013Chatzopoulos et al , 2015Chen et al 2014). A recent arc of radiation hydrodynamical simulations has shown that PI SNe will be visible in the near infrared (NIR) at z ∼ 15 -20 to the James Webb Space Telescope (JWST), the Wide-Field Infrared Survey Telescope (WFIRST) and the Thirty-Meter Telescope (Kasen et al 2011;Cooke et al 2012;Hummel et al 2012;Pan et al 2012;Whalen et al 2013a,c,d,f;de Souza et al 2013de Souza et al , 2014Smidt et al 2014a) and that CC SNe and gamma-ray bursts (GRBs) will be visible out to z ∼ 10 -15 (e.g., Whalen et al 2008a;Moriya et al 2010;Tanaka et al 2012;Whalen et al 2013b,e;Tanaka et al 2013;Mesler et al 2014;Smidt et al 2014b;de Souza et al 2014;Magg et al 2016).…”
Section: Introductionmentioning
confidence: 99%